Performance of pulmonary embolism risk scores in predicting mortality in patients with acute pulmonary embolism - Doaa M. Magdy; Suzan Salama; Nourhan S. Abdelraheem; Sahar R. Mahmoud (Egyptian Journal of Chest Disease and Tuberculosis)
Background The overall mortality rate from acute pulmonary embolism (PE) may be increased up to 20% relying on patients factors at first presentation. Thus, management decisions are mainly dependent on the estimation of the risk of mortality. Aim To compare the prognostic accuracies of different risk assessment scores (PESI score, PERFORM score, and Shock index) in predicting mortality in patients diagnosed with acute PE. Patients and methods 60 patients presented with PE diagnosed by computed tomography pulmonary angiogram (CTPA) were conducted in this study. Demographics (age, sex, smoking status, and risk factors) were recorded. Pulmonary embolism severity index (PESI), PERFORM score, and Shock index were calculated on hospital admission. Results A number of 60 CTPA confirmed PE cases were included in the current study, and the mean age of 50.03 years; 66.7% were females and 30% were current smokers. The predictive ability of different studied scores for prediction of mortality by using the Receiver Operating Characteristic curve analysis was as follows: for PESI score at a cutoff point greater than or equal to 85 points; the area under the Receiver Operating Characteristic curve area under the curve (AUC) was 92.3% having a sensitivity of 85.2% and specificity of 100%. While PERFORM score at a cutoff value of greater than or equal to 6 points; the AUC was 75.8% with a sensitivity of 80% and specificity of 72.2%. For shock index at a cutoff value of greater than or equal to 1.06 points; the AUC was 75.5% with a sensitivity of 80% and specificity of 70%. It was observed that the older age group, lower PaO2, higher PESI score, higher PERFORM score, and higher shock index were significant predictors for mortality. Conclusion PESI score is more effective in predicting mortality of PE patients than the PERFORM score and Shock index.